ANALISIS VARIANS ANGGARAN PENDAPATAN DAN BIAYA PADA KOPERASI SERBA USAHA KARYAWAN UNSOED (KOSUKU) PURWOKERTO - Eling Purwanto Jati (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2007)
This research entiled “Variance Analysis of Incomes and Cost Budget in Multi- Trade Cooperation of Jenderal Soedirman University Employee (KOSUKU) of Purwokerto”. (Case study in Multy-Trade Cooperation of Jenderal Sedirman University Employee of Purwokerto). This research aimed to evaluate the deviation between incomes and cost budget that arranged by KOSUKU and its realization, and to analyze the cause of deviation thet reviewed from the operational of incomes and cost budget.The one of valuation criteria based on Decision of Cooperation State and Small- Middle Trade Minister Number 129/Kep.M.KUKM/XI/2002 about Cooperation Classification Direction is used. Based on variance analysis result, it gained that from three periods of budgeting that evaluated, only 2004 budget that experience difference up to toleration limit. Nonetheless, Trade Gain Residual difference toward budget during 2002-2004 budget period is remain in toleration limit of valuation criteria that stated by Cooperative State and Small-Middle Trade Minister, that is > 100 %.To make perfect the budget arrangement at KOSUKU, it should investigate the buget difference occurred. Then, budget planning that stated in Annual Member Meetingmust be used as direction in cooperation trade application, according to target plannedprior, in order to improve cooperation progress.